Impacto do bullying em outcomes educacionais : evidência brasileira - Vaz, Antônio Carlos da Silva Batista (2021)
This work aims to estimate the effect of being bullied on Mathematics and Portuguese Language grades on the school performance of 6th and 7th grade students, with an average age of 12 years, from public schools located in the city of Recife, seeking to isolate the influence the effects of the school, the community, such as the socioeconomic characteristics of the student, the student's family and their classmates. The work methodology foresees the use of statistical models to measure the impact effects on learning. Thus, the Propensity Score Matching (PSM) will be used combined with the Differences in Difference model (diff-in-diff) in order to compare students who claim to have suffered bullying (treated), with students who have not. Econometric techniques are used to circumvent potential endogeneity problems. The results obtained that there may be a dissipation of the effect of bullying on students' school performance in the short term, in addition to possible selection bias.